PENGARUH PENERAPAN SISTEM ADMINISTRASI PERPAJAKAN MODERN TERHADAP KEPATUHAN WAJIB PAJAK PADA KANTOR PELAYANAN PAJAK MEDAN TIMUR - FITRIANI SARAGIH (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA)
ABSTRACT This study aims to know the effect of organizational structure on the obedience assessable, the influence of organizational procedures on the obedience assessable, the influence of the organizational strategy on the obedience assessable, and the influence of organizational culture on the obedience assessable.Based on the values of regression for the independent variable concluded that the biggest influence on the Taxpayer Compliance is the value of the Organizational Procedure at 0.860 followed by Organizational Culture at 0.221 and followed by the Organizational Strategy at -0.041, and for the next is Organizational Structure at -0.035. Based on the description is known that the increase of the obedience assessable. The result of F test showed no effect of Organizational Structure, Organizational Procedures and organizational strategy on tax compliance. The results of multiple correlation known positive (0.954) indicates that Organizational Structure, Organizational Procedures and organizational strategies gave positive effect jointly (directional) with tax compliance. The results of the correlation value is known that the procedure has no effect on the performance of the Organization at 0.924 then organizational strategies affect the performance at 0.920 and Organizational Structure effect at 0.878. Based on the value of a positive correlation can be seen that any increase in the Organizational Structure, Organizational Procedures and organizational strategies, so the taxpayer compliance is also tend to increase. Keywords :Compliance Taxpayers,Taxation Administration System